Adding "Process Algebra" to TLA - Lamport, Leslie (1995)
At the Dagstuhl workshop described in the discussion of [114], I was impressed by the elegance of the process-algebraic specification presented by Rob van Glabbeek. The ability to encode control state in the process structure permits one to express some specifications quite nicely in CCS. However, pure CCS forces you to encode the entire state in the process structure, which is impractical for real specifications. I had the idea of trying to get the best of both worlds by combining CCS and TLA, and wrote this preliminary note about it. I hoped to work on this with van Glabbeek but, although he was interested, he was busy with other things and we never discussed it, and I never did anything more with the idea. When I wrote this note, I wasn't sure if it was a good idea. I now think that examples in which adding CCS to TLA would significantly simplify the specification are unlikely to arise in practice. So, I don't see any reason to complicate TLA in this way. But, someone else may feel otherwise.